1969
DOI: 10.12669/pjms.312.6956
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dyspepsia symptoms and its correlation with the quality of life among Qashqai Turkish migrating nomads in Fars Province, Southern Iran

Abstract: Objectives:To determine the prevalence of dyspepsia and its correlation with quality of life in Fars Qashqai Turkish migrating nomads from Southern Iran.Methods:During 2010 we enrolled 397 Qashqai migrating nomads from Southern Iran who were 25 years of age or older. Participants completed a questionnaire that consisted of demographic factors, lifestyle data, gastrointestinal symptoms, and the Short-Form 36 Health Survey (SF-36) questionnaire.Results:There was a 48% prevalence of dyspepsia symptoms among parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The minimum and maximum prevalence of dyspepsia pertained to the studies by Moghimi-Dehkordi et al 18 (2.2%) and Yazdanpanah et al 23 (54.6%), respectively. The prevalence of dyspepsia, after removing two high-prevalence studies (Yazdanpanah et al 23 and Masoumi et al 27 ), was 11.3% (95% CI: 7.4-16.7) (Figure 2B).…”
Section: Prevalence Of Dyspepsiamentioning
confidence: 95%
See 1 more Smart Citation
“…The minimum and maximum prevalence of dyspepsia pertained to the studies by Moghimi-Dehkordi et al 18 (2.2%) and Yazdanpanah et al 23 (54.6%), respectively. The prevalence of dyspepsia, after removing two high-prevalence studies (Yazdanpanah et al 23 and Masoumi et al 27 ), was 11.3% (95% CI: 7.4-16.7) (Figure 2B).…”
Section: Prevalence Of Dyspepsiamentioning
confidence: 95%
“…14 Many researchers have investigated the prevalence of dyspepsia in the Iranian population, but the results are not consistent. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Thus, a coherent survey of all documents and combining them can provide a more comprehensive picture of the dimensions of this illness in Iranian community. The results of this meta-analysis can provide a more accurate estimate regarding the effect of therapies or risk factors for the illness or other results through combining different studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this study age, gender, smoking and inadequate physical activities found to be commonest risk factors of functional dyspepsia. On other hand in a south Iranian study of Masoumi SJ et al [14] observed that there was a significant association occurred between the symptoms of dyspepsia and dairy products consumptions, tea before and after food, smoking, uses of non-steroid anti-inflammatory drugs and drinking water, reflux, dysphagia, heartburn, and uses of acetaminophen. Recently Koloski NA et al [15] reported that the correlation keeps on significant for the moderate exercise, gender, independent of age, BMI and the smoking, though role of the exercise in pathophysiology of the symptoms of functional dyspepsia is generally not known [15].…”
Section: Discussionmentioning
confidence: 94%
“…[4,9] However, it is very important because it is a common disease, has a chronic process, adversely affects daily life and quality of life, and increases unjustifiable costs related to health system. [10][11][12][13] In the United States, the annual cost of dyspepsia is more than $ 18 billion. [4,13] Emergency services are healthcare centers, which are easily accessible to receive healthcare services and provide free service to every patient with social security insurance in our country.…”
Section: Introductionmentioning
confidence: 99%